The dynamics of mito‐nuclear coevolution: A perspective from bivalve species with two different mechanisms of mitochondrial inheritance. (14th February 2019) - Iannello, Mariangela; Puccio, Guglielmo; Piccinini, Giovanni; Passamonti, Marco; Ghiselli, Fabrizio
Abstract: The proteins involved in the main process of energy production of most eukaryotes (oxidative phosphorylation, OXPHOS) are encoded by either nuclear or mitochondrial genomes. The importance of mito‐nuclear interactions suggests that the two genomes might be under coevolution. While most eukaryotes are characterized by a strictly maternal inheritance (SMI) of mitochondria, some bivalves show doubly uniparental inheritance (DUI), where two distinct mitochondrial lineages coexist in the same individual, and the nuclear OXPHOS genes have to cofunction with genes produced by two different mitochondrial genomes. We took advantage of the natural heteroplasmy of a DUI species to get insights into the dynamics of mito‐nuclear coevolution. We used RNA‐seq to investigate transcription and rate of protein evolution of OXPHOS genes in two related bivalves: Ruditapes decussatus (Bivalvia, Veneridae), a species with SMI, and Ruditapes philippinarum (Bivalvia, Veneridae), a species with DUI. Surprisingly, our results are not consistent with most of the proposed hyphotheses about the mechanisms of mito‐nuclear coevolution. In particular, despite observing a rate of protein evolution of mitochondrial subunits an order of magnitude higher compared to that of most animal taxa investigated so far, we found no evidence for nuclear compensation. Moreover, we found no correlation between rate of protein evolution and transcription level in both nuclear and mitochondrial OXPHOS subunits. In this work, we report clear deviations from the expected results predicted by widely accepted hypotheses built around data obtained from a restricted representation of biodiversity. This should encourage further investigations based on broad comparative analyses encompassing usually overlooked non‐model species. Abstract : The proteins involved in oxidative phosphorylation are encoded by either nuclear or mitochondrial genomes. Given the importance of mito‐nuclear interactions, the two genomes should experience coevolution. We studied the dynamics of mito‐nuclear coevolution in the bivalves Ruditapes decussatus and Ruditapes philippinarum . We report clear deviations from the expected results predicted by hypotheses built around data obtained from a restricted representation of biodiversity. These findings encourage investigations based on comparative analyses encompassing overlooked non‐model species.